Navigating Total Ankle Replacement: A Patient's Guide Through the Web - Jared Van Vleet BS; Samuel Shepard DO; Amar Patel DO; Cameron OBrien BS; Griffin Hughes BS (Foot & Ankle Orthopaedics)
Category: Ankle; Arthroscopy Introduction/Purpose: Ankle osteoarthritis, primarily posttraumatic, affects younger patients with extended life expectancies, significantly impacting their physical and mental quality of life. Surgical interventions, such as ankle fusion and ankle replacement, are crucial for managing end-stage ankle osteoarthritis. Ankle fusion has been the gold standard, providing consistent symptom relief, while total ankle arthroplasty (TAA) has evolved with improved designs and biomechanical properties. Studies indicate a notable increase in TAA rates compared to total knee and hip arthroplasty. However, the debate continues regarding the long-term outcomes and risk-benefit analysis of TAA versus ankle fusion, with individual patient characteristics and functional demands playing a significant role in treatment decisions. Methods: We conducted a study to analyze information related to total ankle replacement procedures. Using Google searches and the SEO minion Chrome extension, we collected and categorized 100 FAQs from reliable sources. We used the Rothwell classification for FAQ transparency, evaluated source transparency using the JAMA benchmark tool, and assessed source quality with Brief DISCERN. Statistical analysis was performed in R(4.3.1) and RStudio, including descriptive statistics, Fisher’s exact test for JAMA Benchmark item presence, and the Kruksal-Wallis test for website category differences in Brief Discern Scores. Dunn’s test was used for post-hoc analysis with Holm correction for multiple comparisons. Results: Our Google search returned 100 unique FAQs after removing duplicates and unrelated FAQs. The majority were classified as fact-based questions (47/100, 47%), followed by value (30/100, 30%) and policy questions (23/100, 23%). Overall, the most common topic searched was related to the timeline of recovery (17/47, 36.2%). The frequent answer sources were medical practice/hospital (44/100, 44%), followed by academic (27/100, 27%) and government (24/100, 24%). The Kruksal-Wallis test revealed a significant difference in mean quality scores among the 4 source types (H(3) = 8.7445, p = 0.03) with medical practices/hospitals averaging the worst score (16/30) compared to academic sources which were found to have the highest score (22/30). Conclusion: When seeking online information regarding total ankle replacement surgery, patients using Google most often searched fact-based questions pertaining to the timeline of recovery. Medical practices and hospitals were the most common sources for this information but scored the lowest in quality and transparency. When publishing online information, sources should refer to established criteria such as the JAMA benchmark tool and Brief DISCERN. Based on our results physicians should be informed of the fact that patients do not commonly encounter high-quality information. This emphasizes the importance of well-informed, evidence-based patient counseling prior to treatment.